Pakistan Handbook - Shaw, Isobel (Chico, California Moon Publications INC., 1998)
The second edition of a MOON TRAVEL HANDBOOK which provides information and advice for visitors to Pakistan, from an outline of Pakistani culture, history and geography to such practicalities as visas, accommodation, restaurants and transportation. Last published in 1989.
Include Color Illustration, Appendix and Index
Keywords: Pakistan -- Pakistan -- Guidebooks